Best Position Method for Experimental Data Acquisition Systems Using Low-cost GPS Receiver - Abba, I.; Abidin, W.A.W.Z; Othman, A.K.; Hong Ping, Kismet; Abdullah, M.; Voon Pai, B. (IEEE, 2011)
Mobile satellites (MS) propagation is important for the study of satellites signal strength. This paper concentrates on the evaluation of best positioning for the experimental data acquisition system, where a portable commercial Global Positioning System receiver was used in getting the best position. The receiver azimuth angle and elevation angle were utilized in obtaining the best results. The experiment is carried out in an open space area where line-of sight will be visible. Measurement is then performed to determine the relationship between the signal performance with respect to the elevation and azimuth angles. The result obtained from this experiment will be used to set a standard and best positioning for the GPS receiver in collecting data for experimental purpose. Single frequency receivers have the advantage that they are low-cost and CA-code acquisition for civilian access provide higher signal to noise ratio than synthesized P-code acquisition. Since the civilian users can have only access of CA-code, while the P-code in mainly for military users, this kind of receiver was used in this research. Details methodology for doing the experimental works will be discussed. The experiment was conducted at roof top of faculty of engineering building, Universiti Malaysia Sarawak. Therefore, a handheld GPS receiver best positioning experiment designed in order to encourage more experimental works to be carried out in the less developed countries. The analysis of the signal performance under different MS environments is performed with respect to the information such as elevation and azimuth angles.